Effect of Annealing on the Development of Fully Transparent Ternary V-O-Na-Si Mixed Metal Oxide Thin Films from Polymer-Assisted Dip-Coated V2O5. (7th October 2015) - O'Hanlon, Sally; Glynn, Colm; O'Dwyer, Colm
Abstract : Both transparent oxides and transparent conductive oxides are of particular research interest for future applications in flexible, optically transparent thin film transistors and luminescent devices. We report the formation of a transparent oxide material based on the interdiffusion of Na-O and Si-O species with dip-coated V2 O5 thin films on a borosilicate glass substrate. The deposition process used a facile solution processed dip-coating technique in the high-rate draining regime. Liquid precursors of vanadium alkoxide and alkoxide-polyethylene glycol mixtures were used for thin film deposition. We examine the effect of annealing condition on the phase conversion process, morphology and optical transmittance due to the conversion of the V2 O5 films to completely transparent ternary mixed metal oxide thin films. The work also examines the role of polymer-assisted deposition on the development of the V-O-Na-Si transparent thin films during different annealing conditions. Polymer-assisted V2 O5 thin films on glass are shown to convert to optically clear thin films during annealing, with a transparency >95% across the visible spectrum, and a blue-shift of the absorption edge to maintain >90% transparency at 380 nm.